1977
DOI: 10.2466/pr0.1977.40.2.671
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Correlations for the State-Trait Anxiety Inventory

Abstract: For 100 to 105 students who were tested before and after a 45-min. classroom examination, test-retest correlations ranged from .66 (first and second administrations of A-State of State-Trait Anxiety Inventory) to .83 (second administration of A-Trait and second administration of A-State).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…The low test-retest reliability in the Sanxiety scale confirms the nature of the S-anxiety. The similar results were reproduced by Joesting (1977), and Nixon and Steffeck (1977). Joesting (1977) found that test-retest reliability, obtained by administering the STAI before and after a class examination, was lower in the Sanxiety (.66) than the T-anxiety scale (.83).…”
Section: Anxietysupporting
confidence: 61%
See 1 more Smart Citation
“…The low test-retest reliability in the Sanxiety scale confirms the nature of the S-anxiety. The similar results were reproduced by Joesting (1977), and Nixon and Steffeck (1977). Joesting (1977) found that test-retest reliability, obtained by administering the STAI before and after a class examination, was lower in the Sanxiety (.66) than the T-anxiety scale (.83).…”
Section: Anxietysupporting
confidence: 61%
“…The similar results were reproduced by Joesting (1977), and Nixon and Steffeck (1977). Joesting (1977) found that test-retest reliability, obtained by administering the STAI before and after a class examination, was lower in the Sanxiety (.66) than the T-anxiety scale (.83). Also, Nixon and Steffeck (1977) confirmed lower test-retest reliability of the S-anxiety scale over 3, 8, and 11-month period in college student sample.…”
Section: Anxietysupporting
confidence: 61%
“…Satisfactory evidence of concurrent validity of the STAI-T scale and construct validity of the STAI-S scale was reported (Spielberger, 1970). Highly acceptable test-retest reliability coefficients have been reported for the STAI-T scale but not for the STAI-S scale as were anticipated, because a valid measure of STAI-S should reflect the influence of unique situational factors existing at the time of testing (Joesting, 1977;Newmark, 1972;Spielberger, 1970). The standard scoring procedure was followed and the two distinct subscales were to be used separately in the main analysis for this study.…”
Section: The Personal Autonomy Inventory (Pal)mentioning
confidence: 76%
“…In a study by Joesting (1977), 105 educational psychology students were tested with the STAI and retested after a 45-minute class. The correlation reported for the A-state measure was .66, while the correlation for the A-trait was .81.…”
mentioning
confidence: 99%